DlERF98 transcription factor mediates salicylic acid-induced disease resistance in postharvest longans by activating phenylpropanoid metabolism - Qi Chen; Zhongqi Fan; Ruiling Zhuo; Yifen Lin; Hui Wang; Boqiang Li; Shiping Tian; Mengshi Lin; Hetong Lin; Yihui Chen (Postharvest Biology and Technology, 2026)

Energy metabolism participates in DNP- or ATP-mediated regulation of pulp breakdown in Phomopsis longanae Chi-infected longans - Yuzhao Lin; Shujuan Feng; Zhengwei Chen; Ruiling Zhuo; Shucheng Li; Yueying Sang; Yihui Chen; Boqiang Li; Shiping Tian; Yifen Lin; Hetong Lin (Postharvest Biology and Technology, 2026)

Selective iron removal from Fe-PGMs alloys for platinum group metals concentration: Dissolution behavior of PGMs and ultrasound-assisted leaching - Han Yang; Yong Li; Xilong Wu; Ruiling Yuan; Chao Wang; Shengnan Lin; Jibiao Han; Kuo Liu (Journal of Environmental Chemical Engineering, 2026)

Quantitative proteomics reveals energy metabolism remodeling in Bacillus cereus spores under pulsed light treatment - Ruiling Lv; Jiawei Liu; Qin Li; Yajin Qi; Jianwei Zhou; Shao Chen (Food Research International, 2026)

Effects and mechanisms of different metastable systems on the interfacial stability and physicochemical properties of ovalbumin emulsion gels - Zongqi Yang; Lili Shi; Ruiling Li; Yi Song (Food Chemistry, 2026)

Inactivating Bacillus cereus spores with pulsed light: roles of thermal and reactive oxygen species-mediated mechanisms - Qin Li; Jiawei Liu; Jianwei Zhou; Donghong Liu; Yajin Qi; Ruiling Lv (Food Research International, 2026)

A resilience-based approach to safety barrier performance assessment of blended hydrogen natural gas pipeline system - Ruiling Li; Guojin Qin; Guoqing Xiao; Yihuan Wang (Process Safety and Environmental Protection, 2026)

DCC and ADP modulate the disease progression in postharvest longan caused by Phomopsis longanae Chi in relation to ROS metabolism and cell wall integrity - Xiang Gao; Xiaoxuan Wang; Wenjing Lin; Huili Zhang; Ruiling Zhuo; Yihui Chen; Boqiang Li; Shiping Tian; Hetong Lin; Yifen Lin (Postharvest Biology and Technology, 2026)

Involvements of energy metabolism, disease defense system and cell wall integrity in 2,4-dinitrophenol and adenosine triphosphate-mediated energy state modulating disease occurrence in fresh longan incurred by Phomopsis longanae Chi - Yueying Sang; Mengyin Chen; Yifen Lin; Ruiling Zhuo; Yihui Chen; Shiping Tian; Boqiang Li; Hetong Lin (Postharvest Biology and Technology, 2026)

A Comparative Study on the Efficiency Process of Cellulosic Wastewater Fermentation by Oleaginous Yeasts - Shimiao Yao; Hailong Li; Ruiling Gao; Xuefang Chen; Can Wang; Lian Xiong; Xinde Chen (Indian Journal of Microbiology, 2026)

Slightly acidic electrolyzed water enhances fruit disease resistance in longans by activating phenylpropanoid and flavonoid pathways - Qingqing Liu; Shengtai Lin; Yuxin Wu; Zhongqi Fan; Ruiling Zhuo; Yifen Lin; Boqiang Li; Shiping Tian; Mengshi Lin; Hetong Lin; Yihui Chen (Postharvest Biology and Technology, 2026)

DlNAC41 and DlNAC100 transcription factors modulate longan pulp breakdown via adjusting the expression of cell wall degradation-related genes - Hui Wang; Wenlong Zhou; Xinyue Mu; Zhongqi Fan; Ruiling Zhuo; Yihui Chen; Wangjin Lu; Boqiang Li; Shiping Tian; Yifen Lin; Hetong Lin (Postharvest Biology and Technology, 2026)

DNP and ATP-induced the variation of respiration metabolism participate in the regulation of perishability in fresh longan incurred by Phomopsis longanae Chi - Shucheng Li; Yuzhao Lin; Wen Lin; Yifen Lin; Ruiling Zhuo; Yihui Chen; Mengshi Lin; Shiping Tian; Boqiang Li; Hetong Lin (Postharvest Biology and Technology, 2026)

Application of ε-poly-L-lysine alleviates postharvest disease in fresh longans incurred by Phomopsis longanae Chi via regulating the metabolisms of reactive oxygen species and membrane lipids - Xiaoze Dai; Qingqing Liu; Junzheng Sun; Ruiling Zhuo; Yifen Lin; Mengshi Lin; Boqiang Li; Shiping Tian; Hetong Lin; Yihui Chen (Postharvest Biology and Technology, 2026)

DlbHLH66 transcription factor is involved in the acidity differences in the pulp of fresh longan cv. ‘Fuyan’ and ‘Dongbi’ during storage - Zhongqi Fan; Lingzhen Zeng; Shucheng Li; Hui Wang; Ruiling Zhuo; Yifen Lin; Yihui Chen; Wangjin Lu; Boqiang Li; Shiping Tian; Hetong Lin (Postharvest Biology and Technology, 2026)

Performance evaluation of sulfur autotrophic denitrification technology, AO process and anaerobic MBR for treating real mineral processing wastewater - Yilin Shang; Ruiling Luo; Yue Yang; Jiansheng Li (Journal of Environmental Chemical Engineering, 2026)

Involvements of dicyclohexylcarbodiimide and adenosine diphosphate-mediated respiration and organic acid metabolisms in pulp acidification of Phomopsis longanae Chi-infected longan fruit - Weiting Bi; Yueying Sang; Wen Lin; Ruiling Zhuo; Mengshi Lin; Yihui Chen; Boqiang Li; Shiping Tian; Yifen Lin; Hetong Lin (Food Chemistry, 2026)

Sustainable corecovery of lithium, rubidium, and cesium from lepidolite via calcium chloride–sodium lignosulfonate roasting integrated with precipitation–solvent extraction - Guangyu Duan; Ruiling Du; Guangqian Li; Xin Ma; Zhanfang Cao; Hong Zhong; Shuai Wang (Chemical Engineering Journal, 2026)

Comparative analysis of pulp breakdown, autophagy activity, and AsA-GSH cycle in postharvest 'Fuyan' and 'Dongbi' longan - Yueying Sang; Shucheng Li; Ruiling Zhuo; Mengshi Lin; Yihui Chen; Boqiang Li; Shiping Tian; Hetong Lin; Yifen Lin (Postharvest Biology and Technology, 2026)

Spatiotemporal Evolution and Influencing Factors of China’s Airport Carbon Emissions - Ruiling Han; Jingcong Sun; Zongzhe Li; Xiaoyan Zhang; Shikai Song (Chinese Geographical Science, 2026)

The changes of antioxidant system, membrane integrity and phenolics metabolism participate in bongkrekic acid and adenosine triphosphate-mediated energy status regulating longan pericarp browning - Meiling Li; Hetong Lin; Ruiling Zhuo; Boqiang Li; Yifen Lin; Yihui Chen; Zhongqi Fan; Hui Wang (Postharvest Biology and Technology, 2026)

EBV-miR-BART14-3p Targets LACTB to Enhance Gastric Cancer Cell Proliferation and Migration - Xiaomin Huang; Xuhui Zhao; Yujiao Qi; Tian Lan; Ruiling Wang; Shuang Liang; Yuxiu Ma; Cuixia Di; Hongling Li (Biochemical Genetics, 2026)

Dynamic changes in epidermal wax composition and quality of three goji berry varieties during postharvest storage - Ben Niu; Zihao Zong; Yifan Ding; Huizhi Chen; Weijie Wu; Maratab Ali; Mohamed A. Farag; Xiangjun Fang; Ting Huang; Chaoyi Shen; Li-shu Wang; Ruiling Liu; et al. (Postharvest Biology and Technology, 2026)

Exploring the potential of ultrasound to improve the physicochemical properties of protein-based emulsion gels: by ultrasonically treating emulsion (pre-emulsification, post-emulsification) and substrate solution respectively - Ruiling Li; Chao Ma; Ningzhe Wang; Jing Wang; Xin Yang (Food Hydrocolloids, 2025)

Comparative transcriptomic and metabolomic analyses reveal the role of acidic electrolyzed-oxidizing water in enhancing disease resistance in Phomopsis longanae Chi-infected longans - Meiling Li; Zhongqi Fan; Xiaoze Dai; Mengshi Lin; Yifen Lin; Hui Wang; Ruiling Zhuo; Yen-Con Hung; Hetong Lin; Yihui Chen (Postharvest Biology and Technology, 2025)

The transcription factor CeWRI3 functions in TAG accumulation through activating CeOLE2 in Cyperus esculentus - Zhi Zou; Xiaowen Fu; Na Li; Panyan Zheng; Ruiling Wang; Hongyan Liu; Jiaquan Huang; Yongguo Zhao (Plant Cell Reports, 2025)

Effect and mechanism of ultrasound time and storage time on physicochemical properties, 3D printing accuracy, and microstructure of ovalbumin–gellan gum emulsion gels - Ruiling Li; Ningzhe Wang; Chao Ma; Jiacheng Wang; Jing Wang; Xin Yang (Food Chemistry, 2025)

Digital twin-based risk assessment method for dynamic monitoring of heavy rain disasters in rammed earth city site: a case study of the Puzhou ancient city - Ruiling Zhang; MiaoLe Hou; Youqiang Dong; Yihao Li (Bulletin of Engineering Geology and the Environment, 2025)

Fe-loaded hollow fiber carbon microfiltration membrane and its BPA removal performance based on electro-Fenton - Ruiling Luo; Zhongcheng Yang; Yucheng Wang; Yue Yang; Lanyue Qi; Junwen Qi; Zhigao Zhu; Yujun Zhou; Jiansheng Li (Journal of Environmental Chemical Engineering, 2025)

Construction and formation mechanism of phase-change polysaccharide–protein composite emulsion gels: For simultaneous printing of food products with complex structures and fine patterns - Ruiling Li; Ningzhe Wang; Chao Ma; Jiacheng Wang; Jing Wang; Xin Yang (Food Hydrocolloids, 2025)

The petunia heavy metal P-type ATPase PhHMA5II1 interacts with copper chaperons and regulate Cu detoxification - Liru Pan; Ruiling Li; Jinglei Wu; Yanbang Li (Plant Cell Reports, 2025)

Silk protein: A novel antifungal and edible coating for strawberry preservation - Yan Wang; Weijie Wu; Ruiling Liu; Ben Niu; Xiangjun Fang; Hangjun Chen; Mohamed A. Farag; Li-Shu Wang; Guannan Wang; Hailong Yang; Huizhi Chen; Haiyan Gao (Food Chemistry, 2025)

Mechanical behavior and compositional variation of weathered granite soil with different degrees of weathering - Yi Shan; Kezheng Yang; Ruiling Jia; Yadong Li; Yizhao Wang; Jie Cui (Bulletin of Engineering Geology and the Environment, 2025)

Novel overlapping constructed wetlands with water drops reoxygenation and lightweight fillers for decentralized wastewater treatment - Zhao Shuyuan; Li Guo; Shui Paipai; Nie Wenbo; Qu Han; Yan Jun; Li Hong; Wang Ruiling (Bioresource Technology, 2024)

Amino-functionalized graphene oxide affects bacteria–phage interactions in aquatic environments - Ying Li; Kexin Zhang; Yansong Yin; Xinxin Kong; Ruiling Zhang; Haijun Wang; Zhong Zhang (Water Research, 2024)

A novel function of benzoic acid to enhance intestinal barrier defense against PEDV infection in Piglets - Ruiling Liu; Rongfeng Tang; Yuchen Li; Qiu Zhong; Yunlei Cao; Qian Yang (Veterinary Microbiology, 2024)

Comparative study on the rock breaking performance of constant cross section disc cutter and inserted tooth disc cutter for cutting granite - Laikuang Lin; Ruiling Li; Xingchen Luo; Yimin Xia (Tunnelling and Underground Space Technology, 2024)

3-hydroxycoumarin effectively inhibits development and pathogenicity by targeting Pempk proteins of Penicillium expansum - Ruiling Zhuo; Xiaokang Zhang; Yong Chen; Mengyang Xing; Shiping Tian; Boqiang Li (Postharvest Biology and Technology, 2024)

A comparative study of algal-bacterial granular sludges and aerobic granular sludge at different C/N ratio: Granule characteristics, SND progress and Microbial community - Ruiling Bao; Yunlong Zheng; Cong Ma; Lianqing Xue; Wei Cheng; Aidong Ruan; Xiang Li (Journal of Environmental Chemical Engineering, 2024)

Simulated gastrointestinal digestion of walnut protein yields anti-inflammatory peptides - Wei Xia; Yuan Gao; Xiangjun Fang; Long Jin; Ruiling Liu; Li-Shu Wang; Yangyong Deng; Junlong Gao; Hailong Yang; Weijie Wu; Haiyan Gao (Food Chemistry, 2024)

Effect of solid-state fermentation on the nutritional composition and physicochemical properties of whole-grain highland barley and the application in digestive cookies - Shunzhang Ma; Jilin Dong; Jiayao Li; Yingying Zhu; Yunlong Li; Ruiling Shen (Food Bioscience, 2024)

Correction to: Machine Learning Accelerates De Novo Design of Antimicrobial Peptides - Kedong Yin; Wen Xu; Shiming Ren; Qingpeng Xu; Shaojie Zhang; Ruiling Zhang; Mengwan Jiang; Yuhong Zhang; Degang Xu; Ruifang Li (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Machine Learning Accelerates De Novo Design of Antimicrobial Peptides - Kedong Yin; Wen Xu; Shiming Ren; Qingpeng Xu; Shaojie Zhang; Ruiling Zhang; Mengwan Jiang; Yuhong Zhang; Degang Xu; Ruifang Li (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Drought shortens subtropical understory growing season by advancing leaf senescence - Huanfa Sun; Liming Yan; Zhao Li; Wanying Cheng; Ruiling Lu; Xingli Xia; Jiaye Ping; Chenyu Bian; Ning Wei; Cuihai You; Songbo Tang; Ying Du; et al. (Global Change Biology, 2024)
Subtropical forests, recognized for their intricate vertical canopy stratification, exhibit high resistance to extreme drought. However, the response of leaf phenology to drought in the species‐rich understory remains poorly understood. In this study, we constructed a digital camera system, amassing over 360,000 images through a 70% throughfall exclusion experiment, to explore the drought response of understory leaf phenology. The results revealed a significant advancement in understory leaf senescence phenology under drought, with 11.75 and 15.76 days for the start and end of the leaf‐falling event, respectively. Pre‐season temperature primarily regulated leaf development phenology, whereas soil water dominated the variability in leaf senescence phenology. Under drought conditions, temperature sensitivities for the end of leaf emergence decreased from −13.72 to −11.06 days °C −1 , with insignificance observed for the start of leaf emergence. Consequently, drought treatment shortened both the length of the growing season (15.69 days) and the peak growth season (9.80 days) for understory plants. Moreover, this study identified diverse responses among intraspecies and interspecies to drought, particularly during the leaf development phase. These findings underscore the pivotal role of water availability in shaping understory phenology patterns, especially in subtropical forests.

Failure probability estimation of natural gas pipelines due to hydrogen embrittlement using an improved fuzzy fault tree approach - Guojin Qin; Ruiling Li; Ming Yang; Bohong Wang; Pingan Ni; Yihuan Wang (Journal of Cleaner Production, 2024)

Evaluation of multiscale mechanisms of ultrasound-assisted extraction from porous plant materials: Experiment and modeling on this intensified process - Jiaheng Li; Wenjun Wang; Weidong Xu; Yong Deng; Ruiling Lv; Jianwei Zhou; Donghong Liu (Food Research International, 2024)

Biomimetic hybrid porous microspheres with plant membrane-wall structure for evaluating multiscale mechanisms of ultrasound-assisted mass transfer - Jiaheng Li; Wenjun Wang; Weidong Xu; Songfeng Yu; Ruiling Lv; Jianwei Zhou; Donghong Liu (Chemical Engineering Journal, 2024)

3D Models of Sarcomas: The Next-generation Tool for Personalized Medicine - Ruiling Xu; Ruiqi Chen; Chao Tu; Xiaofeng Gong; Zhongyue Liu; Lin Mei; Xiaolei Ren; Zhihong Li (Phenomics, 2024)

4D food printing: Key factors and optimization strategies - Ningzhe Wang; Ruiling Li; Xibo Wang; Xin Yang (Trends in Food Science & Technology, 2024)

Nanoparticle encapsulation using self-assembly abietic acid to improve oral bioavailability of curcumin - Ying Han; Hua Zhang; Haitian Zhao; Shiyao Fu; Ruiling Li; Zhili Wang; Yangxin Wang; Weihong Lu; Xin Yang (Food Chemistry, 2024)

Persistent free radicals generated from a range of biochars and their physiological effects on wheat seedlings - Ruirui Zhang; Andrew R. Zimmerman; Ruiling Zhang; Penghui Li; Yue Zheng; Bin Gao (Science of The Total Environment, 2024)

Importance sampling-based probabilistic performance modeling of low-, mid- and high-strength pipelines under coupling effect of hydrogen-induced damage and corrosion - Yihuan Wang; Zhenwei Zhang; Siming Liu; Ailin Xia; Ruiling Li; Guojin Qin (Process Safety and Environmental Protection, 2023)

Study on the spatial and temporal correlation and allometric growth mechanism between population aging and carbon emissions in China - Xiaoyang Guo; Ruiling Han; Zongzhe Li; Xiang Zhou (Environmental Science and Pollution Research, 2023)

Protein-based emulsion gels as materials for delivery of bioactive substances: Formation, structures, applications and challenges - Ruiling Li; Yong Guo; Aijun Dong; Xin Yang (Food Hydrocolloids, 2023)

Preparation of heterojunction C3N4/WO3 photocatalyst for degradation of microplastics in water - Xiang Wang; Zhihao Zhu; Jinwei Jiang; Ruiling Li; Junjie Xiong (Chemosphere, 2023)

Effect of influent ammonia nitrogen concentration on the phosphorus removal process in the aerobic granular sludge reactor - Wei Cheng; Cong Ma; Ruiling Bao; Xiaoli Yang; Xuankai Zhou; Yan Liu; Qing Liu; Aidong Ruan; Xiang Li (Journal of Environmental Chemical Engineering, 2023)

Cation engineering in low-dimensional organic-inorganic copper halides for high color rendering index WLEDs - Hong Yin; Wenzhi Li; Zhongyi Wang; Pengyuan Wang; Xin Xu; Peigeng Han; Xin Mao; Feng Liu; Keli Han; Junsheng Chen; Ruiling Zhang (Chemical Engineering Journal, 2023)

Graphene oxide affects bacteriophage infection of bacteria by promoting the formation of biofilms - Xinyu Zhang; Ying Li; Kexin Zhang; Yansong Yin; Jie Wang; Luocheng Wang; Zhexing Wang; Ruiling Zhang; Haijun Wang; Zhong Zhang (Science of The Total Environment, 2023)

Combined effects of NaOH, NaCl, and heat on the characteristics of ovalbumin gel and the exploration of the mechanism of transparent gel formation - Hui Xue; Tianfeng Han; Guowen Zhang; Xiaobo Hu; Ruiling Li; Huilan Liu; Rui Li; Yonggang Tu; Yan Zhao (Food Hydrocolloids, 2023)

Extraction of Eucommia ulmoides gum and microbial lipid from Eucommia ulmoides Oliver leaves by dilute acid hydrolysis - Ruiling Gao; Hairong Zhang; Bo Li; Haijun Guo; Hailong Li; Lian Xiong; Xinde Chen (Biotechnology Letters, 2023)

Extensive regulation of pH-responsive transcription factor PacC on secondary metabolism contributes to development and virulence of Botrytis cinerea - Ruiling Zhuo; Guangjin Li; Huaimin Peng; Yuanyuan Zong; Xiao Wang; Shasha Lu; Yong Chen; Zhanquan Zhang; Shiping Tian; Boqiang Li (Postharvest Biology and Technology, 2023)

Regulating cobalt chemical state by CeO2 facets preferred exposure for improved ethanol steam reforming - Ruiling Li; Chengyuan Liu; Li Li; Junjie Xu; Jinjin Ma; Jiaqi Ni; Jing Yan; Jun Han; Yang Pan; Yi Liu; Lilin Lu (Fuel, 2023)

In vitro fermentation characteristics of the dietary fiber in bamboo (Phyllostachys edulis) shoots and its regulatory effects on the intestinal microbiota and metabolites - Weijie Wu; Qi Li; Hangjun Chen; Xiangjun Fang; Ben Niu; Ruiling Liu; Honglei Mu; Haiyan Gao (Food Chemistry, 2023)

Application of melatonin delays lignification in postharvest water bamboo shoots in association with energy metabolism - Baiqi Yang; Yanchao Han; Haiyan Gao; Ruiling Liu; Feng Xu; Ruihai Liu; Shangyue Xiao; Bin Li; Hangjun Chen (Postharvest Biology and Technology, 2023)

A prognostic cuproptosis-related lncRNA predictive signature for bladder cancer patients - Shaoqin Jiang; Jili Zhang; Qi Fan; Zhihao Li; Ruiling Dou; Zequn Lin; Zhenlin Chen; Yue Xu; Zhangcheng Huang; Jingyuan Lan; Wenwen Lin; Sijie Xu; et al. (Human Cell, 2023)

An integrated modeling method of uncertainties: application-orientated fuzzy random spatiotemporal analysis of pipeline structures - Yihuan Wang; Ruiling Li; Ailin Xia; Pingan Ni; Guojin Qin (Tunnelling and Underground Space Technology, 2023)

Aquatic environmental fates and risks of benzotriazoles, benzothiazoles, and p-phenylenediamines in a catchment providing water to a megacity of China - Ruiling Zhang; Shizhen Zhao; Xin Liu; Lele Tian; Yangzhi Mo; Xin Yi; Shiyang Liu; Jiaqi Liu; Jun Li; Gan Zhang (Environmental Research, 2023)

Fe-ZIF-derived hollow porous carbon nanofibers for electromagnetic wave absorption - Ruiling Sun; Guilong Yan; Xunlong Zhang; Zhenyu Li; Jingyu Chen; Li Wang; Yuanpeng Wu; Yiqun Wang; Han Li (Chemical Engineering Journal, 2023)

Treatment of Wastewater-CPL by Biochar-Based Fenton-Like Catalyst in the Presence of Micro-nano Bubbles - Ruiling Zhang; Jiajun Wang; Jianyu Yang; Songyan Qin; Feiyue Li; Lixin Zhao; Zhe Zhu (Water, Air, & Soil Pollution, 2022)

Indiscriminate Dietary Compositions of Two Asian Horseshoe Crabs, Tachypleus tridentatus and Carcinoscorpius rotundicauda: Evidence from Hemolymph Stable Isotopes - Yuhong Li; Jianxiang Feng; Kit Yue Kwan; Yiran Tan; Bosen Weng; Ruiling Jia (Journal of Ocean University of China, 2022)

The Mechanism of Stem Cell Aging - Liangyu Mi; Junping Hu; Na Li; Jinfang Gao; Rongxiu Huo; Xinyue Peng; Na Zhang; Ying Liu; Hanxi Zhao; Ruiling Liu; Liyun Zhang; Ke Xu (Stem Cell Reviews and Reports, 2022)
Stem cells have self-renewal ability and multi-directional differentiation potential. They have tissue repair capabilities and are essential for maintaining the tissue homeostasis. The depletion of stem cells is closely related to the occurrence of body aging and aging-related diseases. Therefore, revealing the molecular mechanisms of stem cell aging will set new directions for the therapeutic application of stem cells, the study of aging mechanisms, and the prevention and treatment of aging-related diseases. This review comprehensively describes the molecular mechanisms related to stem cell aging and provides the basis for further investigations aimed at developing new anti-stem cell aging strategies and promoting the clinical application of stem cells.

Spatial-temporal Evolution Characteristics and Decoupling Analysis of Influencing Factors of China’s Aviation Carbon Emissions - Ruiling Han; Lingling Li; Xiaoyan Zhang; Zi Lu; Shaohua Zhu (Chinese Geographical Science, 2022)

Efficacy and safety of aripiprazole once-monthly versus oral aripiprazole in Chinese patients with acute schizophrenia: a multicenter, randomized, double-blind, non-inferiority study - Le Xiao; Qian Zhao; An-ning Li; Jushui Sun; Bin Wu; Lina Wang; Honggeng Zhang; Ruiling Zhang; Keqing Li; Xiaojin Xu; Tiebang Liu; Wenshun Zhang; et al. (Psychopharmacology, 2022)

Biochar Derived from Treated Lotus Stem and Adsorption of Phthalic Acid Esters - Ruiling Zhang; Linlin Chen; Binbin Qiu; Xiaojing Sun; Songyan Qin; Bo Wang; Feiyue Li; Lixin Zhao; Zhe Zhu (Water, Air, & Soil Pollution, 2021)

Correlation between the epigenetic modification of histone H3K9 acetylation of NR2B gene promoter in rat hippocampus and ethanol withdrawal syndrome - Duan Li; Yanqing Zhang; Yanting Zhang; Qi Wang; Qin Miao; Yahui Xu; Jair C. Soares; Xiangyang Zhang; Ruiling Zhang (Molecular Biology Reports, 2019)

Correction to: Identification of β‑carboline and canthinone alkaloids as anti‑inflammatory agents but with different inhibitory profile on the expression of iNOS and COX‑2 in lipopolysaccharide‑activated RAW 264.7 macrophages - Pan Liu; Huixiang Li; Ruiling Luan; Guiyan Huang; Yanan Liu; Mengdi Wang; Qiuli Chao; Liying Wang; Danna Li; Huaying Fan; Daquan Chen; Linyu Li; et al. (Journal of Natural Medicines, 2019)

Identification of β-carboline and canthinone alkaloids as anti-inflammatory agents but with different inhibitory profile on the expression of iNOS and COX-2 in lipopolysaccharide-activated RAW 264.7 macrophages - Pan Liu; Huixiang Li; Ruiling Luan; Guiyan Huang; Yanan Liu; Mengdi Wang; Qiuli Chao; Liying Wang; Danna Li; Huaying Fan; Daquan Chen; Linyu Li; et al. (Journal of Natural Medicines, 2019)

De novo RNA-seq and functional annotation of Ornithonyssus bacoti - DongLing Niu; RuiLing Wang; YaE Zhao; Rui Yang; Li Hu (Experimental and Applied Acarology, 2018)

Two alphapartitiviruses co-infecting a single isolate of the plant pathogenic fungus Rhizoctonia solani - Ruiling Lyu; Yi Zhang; Qing Tang; Yangyi Li; Jiasen Cheng; Yanping Fu; Tao Chen; Daohong Jiang; Jiatao Xie (Archives of Virology, 2018)

Occurrence, Distribution and Ecological Risks of Fluoroquinolone Antibiotics in the Dongjiang River and the Beijiang River, Pearl River Delta, South China - Ruiling Zhang; Ruijie Zhang; Shichun Zou; Ying Yang; Jun Li; Yinghui Wang; Kefu Yu; Gan Zhang (Bulletin of Environmental Contamination and Toxicology, 2017)

Occurrence and distribution of antibiotics in multiple environmental media of the East River (Dongjiang) catchment, South China - Ruijie Zhang; Ruiling Zhang; Jun Li; Zhineng Cheng; Chunling Luo; Yinghui Wang; Kefu Yu; Gan Zhang (Environmental Science and Pollution Research, 2017)

cDNA library construction of two human Demodexspecies - DongLing Niu; RuiLing Wang; YaE Zhao; Rui Yang; Li Hu; YuYang Lei; WeiChao Dan (Acta Parasitologica, 2017)
The research of

Enhanced viability and neural differential potential in poor post-thaw hADSCs by agarose multi-well dishes and spheroid culture - Xiaoling Guo; Shanyi Li; Qingshan Ji; Ruiling Lian; Jiansu Chen (Human Cell, 2015)

Assessment of heavy metal contamination in the sediments from the Yellow River Wetland National Nature Reserve (the Sanmenxia section), China - Qingli Cheng; Ruiling Wang; Wenhai Huang; Wenlin Wang; Xudong Li (Environmental Science and Pollution Research, 2015)

Development and evaluation of a new interferon-gamma release assay for the diagnosis of tuberculosis infection in HIV-infected individuals in China - Liang Yu; Pingzheng Mo; Zeping Wei; Ruiling Fu; Mai Yang; Binying Ji; Jian Wang; Shu Li; Amie J. Strong; Neal Touzjian; Nicholas Kushner; Xi-En Gui; et al. (Infectious Diseases, 2015)

Using LMDI method to analyze the influencing factors of carbon emissions in China’s petrochemical industries - Tijun Fan; Ruiling Luo; Haiyang Xia; Xiaopeng Li (Natural Hazards, 2015)

Zacopride selectively activates the Kir2.1 channel via a PKA signaling pathway in rat cardiomyocytes - Li Zhang; QingHua Liu; ChengFang Liu; XuWen Zhai; QiLong Feng; RuiLing Xu; XiangLi Cui; ZhiQing Zhao; JiMin Cao; BoWei Wu (Science China Life Sciences, 2013)

A DNA vaccine expressing CFP21 and MPT64 fusion protein enhances BCG-induced protective immunity against Mycobacterium tuberculosis infection in mice - Chun Wang; Zhenhua Chen; Ruiling Fu; Ying Zhang; Lingxia Chen; Li Huang; Jinjin Li; Chunwei Shi; Xionglin Fan (Medical Microbiology and Immunology, 2011)